Peruvian validation and standardization of the TabCAT-brain health assessment - Muñoz-Najar, Andrés; Montemurro, Manuel; Tejada, María del Carmen; Rivera-Fernández, Claudia; Sánchez-Fernández, Miguel; Custodio, Nilton; Possin, Katherine L.; Tsoy, Elena; Lanata, Serggio; Soto-Añari, Marcio (Frontiers in Public Health, 2025)
IntroductionDetecting cognitive impairment in low-educated and marginalized populations may result in under- or over-estimation of diagnoses due to reliance on non-validated approaches and normative data. This study validates and standardizes TabCAT-BHA for older adults living in the Andean region of Peru using regression-based normalization.MethodsTwo hundred fifty-eight participants were assessed with the MMSE, RUDAS, and TabCAT-BHA. Classified as either cognitively healthy or impaired based on Clinical Dementia Rating criteria.ResultsBy incorporating sex, place of residence, age, and years of education as covariates, the TabCAT-BHA demonstrated greater accuracy in detecting cognitive impairment (AUC = 75.3%) compared to the MMSE (AUC = 66.4%) and RUDAS (AUC = 71.4%). After incorporating only significant sociodemographic predictors, TabCAT-BHA obtained better AUC (77.4%) compared to MMSE (66.6%) and RUDAS (71.9%).DiscussionThe TabCAT-BHA proves to be a valid tool for detecting cognitive impairment, and incorporating sociodemographic factors improves its accuracy in marginalized settings of Peru.